Operational Performance: Supply Chain Management Practices Mediated by Competitive Advantage of Packaged Food MSMEs in Padang City - Muthia Roza Linda; Fadhilah Idris; Sutiyem Sutiyem Sutiyem Sutiyem; Suhery Suhery Suhery Suhery; Thesa Alif Ravelby (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2023)
The objective of this study was just to look into the impact of supply chain management practices on operational performance mediated by using the competitive advantage of package food MSMEs in Padang city. The population during the study were all owners or managers of packaged food MSMEs in Padang City. Non-probability sampling with a purposive sampling type was utilized. As a sample size, 185 samples were used. Structural Equation Modelling (SEM) with SmartPLS 3.0 was used to analyze this study. The result of this study indicate that; (1) supply chain management practices have a major and beneficial effect on operational performance; (2) supply chain management practices have a major and beneficial effect on competitive advantage; (3) competitive advantage has a major and beneficial effect on operational performance, and (4) supply chain management practices have a major and beneficial effect on operational performance through competitive advantage as a mediating variable.